Goat producers’ perception of climate change and adaptation strategies in the tropical dry forest of Northern Peru - Temoche Socola, Víctor Alexander; Barrantes, Christian; Godoy, David (Mary Ann Liebert, Inc., 2025)
Climate change affects countries worldwide, challenging economies and livelihoods. It negatively impacts food production due to temperature variability, irregular precipitation, frost, and drought, increasing pressure on agrosilvopastoral resources and reducing agricultural and livestock productivity. In Peru, the tropical dry forest, an ecosystem highly vulnerable to climate change, supports traditional goat farming, a primary livelihood for many, with a population of approximately 256,860 goats in Piura. This ecosystem is particularly sensitive to temperature and precipitation changes, which directly affect forage availability and livestock productivity. This study aimed to determine goat producers' perceptions and adaptation strategies to climate change in Marcavelica, Lancones, and La Brea. Data from 130 goat producers were analyzed using descriptive and multivariate statistics (principal component analysis, multiple correspondence analysis, and cluster analysis). Results showed that goat farming occurs predominantly in extensive systems (84.62%). Most producers (56.9%) acknowledged climate change, perceiving changes in temperature (69.9%), precipitation patterns (100%), soil productivity (79.2%), and water availability (50%). Four producer clusters were identified based on adaptive capacity: excellent (6.16%), good (23.08%), regular (75.38%), and poor (24.62%). Producers with higher education, associativity, and training demonstrated better knowledge and adaptive capacity. Climate change is evident in the dry forest ecosystem, negatively affecting goat farming. These findings underscore the importance of education, technical support, and associativity to enhance producers' resilience and sustain livestock production under climate variability.